Impact of positive end-expiratory pressure and recruitment maneuver on healthy lungs in dogs assessed by functional and anatomical monitoring methods - Mosing, Martina; Waldmann, Andreas D.; Gent, Thom C.; Hosgood, Giselle; Sieber-Ruckstuhl, Nadja S.; Dennler, Matthias; Herrmann, Peter; Unger, Karin (Frontiers in Veterinary Science, 2025)
IntroductionAtelectasis is a common occurrence during anesthesia, and positive end-expiratory pressure (PEEP) ventilation and recruitment maneuvers (RM) can be used to mitigate this. However, both techniques may be associated with side effects in healthy lungs, and close monitoring is indicated. This study aimed to evaluate the effects of PEEP and RM in healthy dogs and to compare functional lung monitoring methods by electrical impedance tomography (EIT), volumetric capnography (VCap), and blood gas analysis with the gold-standard anatomical monitoring provided by computed tomography (CT).Methods and materialsNine healthy Beagle dogs underwent anesthesia and mechanical ventilation three times. After 35 min using zero end-expiratory pressure (ZEEP), CT images, VCap, EIT measurements, and arterial blood gas samples were taken. Thereafter, either (1) ZEEP was continued, (2) PEEP initiated or (3) an RM was performed followed by PEEP. Ten minutes after changing the ventilation mode all measurements were repeated. Only one ventilation mode was employed during each anesthesia.ResultsDuring RM, we found a significant increase in the percentage of overaerated lung (Vhyper) (p < 0.001), while the amount of normally aerated lung (Vnormal), poorly aerated lung and non-aerated lung decreased (p ≤ 0.001). VCap showed an increase in airway dead space (VDaw/VT) (p = 0.002), and a decrease in alveolar dead space (VDalv/VTalv). For PEEP, an increase in airway dead space (p = 0.003) was found. For both groups, the amount of carbon dioxide exhaled per breath (VTCO2,br) decreased (p = 0.001), and EIT showed a shift of the center of ventilation to the dependent lung areas (p = 0.021 and p = 0.046, respectively). Oxygenation was superior in RM compared to ZEEP (p = 0.033). The arterial partial pressure of carbon dioxide decreased in RM (p = 0.012). Positive associations were found between Vhyper and VDaw/VT (p = 0.004), Vhyper and VDaw/VT (p = 0.004), Vhyper and Vnormal with VTCO2,br (p = 0.002 for both). Negative associations were found between Vhyper and VDalv/VTalv (p = 0.004) and non-dependent silent spaces (p = 0.050), and Vnormal with oxygenation (p = 0.030).ConclusionWhile RM may be effective in improving gas exchange, it appears to be not benign in healthy lungs, and PEEP might be the preferable strategy to avoid lung collapse during anesthesia. Functional monitoring – EIT, VCap, blood gas analysis – does not detect changes corresponding to anatomical findings on CT.